Audio Media to Improve Listening Skill - Wahyuniar Wahyuniar; Rezky Uspayanti; Harmita Sari; Sumiati Putri Natalia (Universitas Musamus, 2021)
This study aims to prove and describe whether audio media can improve listening skills especially in listening to news broadcasts. One class consisted of 30 students as the sample namely class VIII.1 of Junior High School 2 Mattiro Bulu, Pinrang Regency. A simple random sampling is a technique in choosing the sample. Written tests and oral tests were the tools in collecting the data. The obtaining data analyzed in descriptive statistical techniques and inferential statistics t-test type. Based on the result of the study, the ability to listen to the news of students in class VIII.1 using audio media is categorized as medium. Students who met the standard Minimum completion criteria were 26 students (87%) get the standard Minimum completion criteria and 4 students (13%) who did not reach the Minimum completion criteria. Therefore, audio media can improve the ability of students to listen to the news. Listening learning fulfills three indicators, including learning quality, learning quantity, and time. Hypothesis test results = 2.682 > t table = 2.045. This shows that the proposed research hypothesis is accepted.